2023
DOI: 10.1111/mpp.13389
|View full text |Cite
|
Sign up to set email alerts
|

degQ associated with the degS/degU two‐component system regulates biofilm formation, antimicrobial metabolite production, and biocontrol activity in Bacillus velezensis DMW1

Chenjie Yu,
Junqing Qiao,
Qurban Ali
et al.

Abstract: The gram‐positive bacterium Bacillus velezensis strain DMW1 produces a high level of antimicrobial metabolites that can suppress the growth of phytopathogens. We investigated the mechanism used by degQ and the degS/degU two‐component system to regulate the biocontrol characteristics of DMW1. When degQ and degU were deleted, the biofilm formation, cell motility, colonization activities, and antifungal abilities of ΔdegQ and ΔdegU were significantly reduced compared to wild‐type DMW1. The expression levels of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…DegQ, a 46-amino acid protein coding for a pleiotropic regulator, can directly stimulate the autophosphorylation of DegS. The activated DegS-P then transfers the phosphoryl group to DegU, and the phosphorylated DegU-P can regulate the expression of related genes [ 8 , 81 ]. The knockout of comA resulted in a significant down-regulation of the expression of degU [ 80 ], indicating that ComA positively regulates the DegS-DegU two-component regulatory system.…”
Section: Enhancing Fengycin Production Through Metabolic Engineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…DegQ, a 46-amino acid protein coding for a pleiotropic regulator, can directly stimulate the autophosphorylation of DegS. The activated DegS-P then transfers the phosphoryl group to DegU, and the phosphorylated DegU-P can regulate the expression of related genes [ 8 , 81 ]. The knockout of comA resulted in a significant down-regulation of the expression of degU [ 80 ], indicating that ComA positively regulates the DegS-DegU two-component regulatory system.…”
Section: Enhancing Fengycin Production Through Metabolic Engineeringmentioning
confidence: 99%
“…It is hypothesized that this regulatory effect may be mediated by DegQ, since ComP-ComA positively regulates the expression of degQ [ 95 , 99 ]. Additionally, previous studies have shown that the yield of fengycin significantly decreased in strains with degU knockout [ 80 , 81 ], and the expression level of fenA was also down-regulated [ 81 ]. Da-Eun et al [ 82 ] substituted the “A” at position 32 of degU with a “T”, resulting in an approximately 2-fold increase in both the transcript level of pps gene cluster and their promoter activity, as well as a similar increase in the production of fengycin.…”
Section: Enhancing Fengycin Production Through Metabolic Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…DegU owning typical helix-turn-helix DNA sequence-binding structures, has an ability to regulate the gene transcription by binding to the promoter regions through phosphorylated DegU (DegU-P) or unphosphorylated DegU [ 81 ]. DegU regulates bacillomycin D biosynthesis positively, and surfactin biosynthesis negatively [ 45 48 ]. In 2016, Mathieu et al [ 46 ] reported that the DegU-DegS system differentially regulates the “K-state” which is a growth-arrested state of cells induced by ComK regulon [ 82 ] in undomesticated wild and laboratory domesticated B. subtilis model strains.…”
Section: Genes Affecting Surfactin Expressionmentioning
confidence: 99%
“…DegU: The response regulator DegU is part of a two-component regulatory system. Phosphorylated DegU activates the transcription of genes involved in iturin biosynthesis, enhancing their expression [79].…”
mentioning
confidence: 99%